Implementasi Etika Administrasi Publik : Langkah Utama dalam Menciptakan Good Governance di Indonesia - Choirulsyah, Darmawan; Azhar, Azhar (Universitas Indo Global Mandiri, 2024)
Ethics plays a crucial role in determining the successful operation of organizations and individuals in public administration. This includes various stages, from the design of organizational structures to policy formulation, implementation, and evaluation of policies and public services. This article explains the ethics of public administration in Good Governance in Indonesia. The research was conducted using qualitative methods, as well as the collection of primary and secondary data. Primary data was obtained from observation, and secondary data was obtained from literature and media studies. The observations that have been made show that Indonesian authorities continue to commit significant violations of the code of ethics. In addition to enforcing the law, the government must also uphold the ethics of public administration to prevent or minimize this problem. To enable a discussion on governance in Indonesia, this paper investigates the ethics of public administration and bureaucracy. The conclusion that can be drawn is that in running the government, public administrators use public administration ethics as a reference because all citizens will be affected by the actions of public administrators. Therefore, public administrators must understand and apply public administration ethics to the regulations to ensure Good Governance. The implications of this research are references to changes in the system that are more.